2021
DOI: 10.1111/ijau.12254
|View full text |Cite
|
Sign up to set email alerts
|

The triggers and consequences of audit team stress: Qualitative evidence from engagement teams

Abstract: This study investigates audit team stress, its triggers and consequences to provide qualitative evidence about what audit team stress is and how its triggers and consequences can influence team stress and audit quality. Audit teams in three different audit firms, including different audit team ranks, discussed team stress experiences from one specific engagement during group and individual interviews. Audit work can be stressful, and its consequences can threaten audit quality. Additionally, shared team stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 122 publications
(230 reference statements)
0
6
0
Order By: Relevance
“…Auditors face excessive workloads when they are confronted with various audit tasks for diverse types of clients to complete in a predetermined period with limited resources and work environment capabilities (Danudoro et al , 2021). Most of the research studies found evidence that role ambiguity, role conflict and role overload have significant effects on burnout (Cropanzano et al , 2003; Fogarty and Kalbers, 2006; Guthrie and Jones, 2012; Shbail, 2018 Annelin and Svanström, 2022). However, Zulaikha and Istiqomah (2021) did not find evidence of the effect of role ambiguity and role overload on burnout.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Auditors face excessive workloads when they are confronted with various audit tasks for diverse types of clients to complete in a predetermined period with limited resources and work environment capabilities (Danudoro et al , 2021). Most of the research studies found evidence that role ambiguity, role conflict and role overload have significant effects on burnout (Cropanzano et al , 2003; Fogarty and Kalbers, 2006; Guthrie and Jones, 2012; Shbail, 2018 Annelin and Svanström, 2022). However, Zulaikha and Istiqomah (2021) did not find evidence of the effect of role ambiguity and role overload on burnout.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The problems and challenges affecting auditors during the pandemic lead to a feeling of increased emotional exhaustion among auditors in many audit firms. The accounting literature claims higher job turnover, poor job performance and dissatisfaction as major consequences of burnout for both auditors and audit firms (Herda and Lavelle, 2012; Annelin and Svanström, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, audit firms that focus on the client rather than efficiency are more likely to conduct AQTB (Johansen and Christoffersen, 2017), and auditors in firms with a high-level quality control and review process engage in less AQTB (Malone and Roberts, 1996). However, little is known about how audit team characteristics can influence AQTB (Annelin and Svanström, 2021).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%